1983
DOI: 10.1042/bj2100621
|View full text |Cite
|
Sign up to set email alerts
|

Coupling ratio of electrogenic Na+-alanine cotransport in isolated rat hepatocytes

Abstract: Na+-alanine cotransport across the cell membrane in isolated rat hepatocytes was studied. Changes in the cell membrane potential associated with the transport of alanine interfere with determination of the Na+-alanine coupling ratio of the cotransport. With valinomycin present to 'clamp' the cell membrane potential, a coupling ratio of 1:1 for the Na+-alanine influx was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…Similarly the release of K from pre-loaded rabbit enterocytes is best described by a single decreasing exponential. The rate constant for this efflux was of the same order of magnitude as that reported for other isolated cells (Kristensen, 1980;Valdeolmillos, Garcia-Sancho & Herreros, 1982). Similar kinetic values for uptake and efflux were obtained using 42K and 86Rb as tracers, validating the use of the more convenient 86Rb isotope in future studies.…”
Section: Cell Viabilitysupporting
confidence: 69%
“…Similarly the release of K from pre-loaded rabbit enterocytes is best described by a single decreasing exponential. The rate constant for this efflux was of the same order of magnitude as that reported for other isolated cells (Kristensen, 1980;Valdeolmillos, Garcia-Sancho & Herreros, 1982). Similar kinetic values for uptake and efflux were obtained using 42K and 86Rb as tracers, validating the use of the more convenient 86Rb isotope in future studies.…”
Section: Cell Viabilitysupporting
confidence: 69%
“…Kristensen (1980) has demonstrated an increase in K permeability of isolated rat hepatocytes associated with Na-coupled alanine uptake and has drawn the same conclusion.…”
supporting
confidence: 61%
“…Higgins, Gebler and Fr6mter (1977) arrived at the same conclusion for the case of Necturus urinary bladder and suggested that this could be explained "... if the passive K-leak permeability were an inherent property of the Na-K pump unit or were regulated by an intracellular feedback mechanism." Recently, Kristensen (1980) has reported that rheogenic Na-alanine co-transport by isolated rat hepatocytes is associated with a fivefold increase in the permeability of the hepatocyte membrane to K and no significant change in cell K content. Indeed, Lee and Armstrong (1972) reported that the intracellular K activity, (K)c, in bullfrog small intestine determined using ion-selective microelectrodes decreased following addition of 3-O-methylglucose to the mucosal solution, and, using similar methods, White (1976) has reported that (K)c in Amphiuma small intestine is the same in the presence and absence of 10raM glucose; although the rate of Na absorption was not measured in these studies, it is fair to assume that it was increased in the presence of these sugars (Schultz, 1977).…”
Section: The Relation Between the "Pump" And "Leak" Properties Of Thementioning
confidence: 99%